The impact of ChatGPT integration on students' conceptual understanding of polynomials in Mathematics learning - Deny Hadi Siswanto; Kintoko; Tarso; Siti Atwano Pisriwati (Universitas Ahmad Dahlan, 2025)
This study investigates the impact of using ChatGPT on students' ability to understand mathematical concepts in polynomial topics. As technology rapidly advances, integrating artificial intelligence into mathematics education is becoming increasingly relevant. This research adopts a quantitative approach with a pre-experimental design, employing a one-group pretest-posttest model. The study involved 28 students from class XI-A at SMA Muhammadiyah 1 Sleman, selected through a non-probability sampling method. The research utilized questionnaires and conceptual understanding tests, both of which were validated for reliability and accuracy using SPSS-25. The findings revealed that incorporating ChatGPT in learning contributed 10.4% to enhancing students' conceptual understanding, with the results of the linear regression test indicating a positive and significant relationship (p = 0.045 < 0.05). A comparative analysis of pretest and posttest scores demonstrated an improvement in students’ conceptual comprehension following the intervention. These results suggest that ChatGPT can serve as an innovative tool in mathematics instruction, aiding students in developing a deeper understanding of mathematical concepts. The study’s implications are expected to offer valuable insights for educators in designing more effective learning strategies and provide recommendations for educational technology developers to enhance AI-based learning features.